Measuring unfair inequality: Reconciling equality of opportunity and freedom from poverty - Paul Hufe; Ravi Kanbur; Andreas Peichl (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
Empirical evidence on distributional preferences shows that people do not judge inequality as problematic per se but that they take the underlying sources of income differences into account. In contrast to this evidence, current measures of inequality do not adequately reflect these normative preferences. In this paper, we address this shortcoming by developing a new measure of unfair inequality that reconciles two idely-held fairness principles: equality of opportunity and freedom from poverty. We provide two empirical applications of our measure. First, we analyze the development of inequality in the US from 1969 to 2014 from a normative perspective. Second, we conduct a corresponding international comparison between the US and 31 European countries in 2010. Our results document increasing unfairness in the US over time. This trend is driven by a strong decrease in social mobility that puts the "land of opportunity" among the most unfair countries in 2010.
Keywords: D31; D63; I32; 330; inequality; equality of opportunity; poverty; fairness; measurement